Autonomic thermoregulatory dysfunction in neurofibromatosis type 1 - Luciana G Madeira; Renata LF Passos; Juliana F de Souza; Nilton A Rezende; Luiz O. C. Rodrigues (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective Neurofibromatosis type 1 (NF1) causes neural and cutaneous disorders and reduced exercise capacity. Exercise/heat exposure increasing internal temperature must be compensated by eccrine sweat function and warmed skin vasodilation. We suspected NF1 could adversely affect eccrine sweat function and/or vascular thermoregulatory responses (VTR). Methods The eccrine sweat function and VTR of 25 NF1 volunteers (14 males, 11 females; 16–57 years old) were compared with 23 non-NF1 controls matched by sex, age, height and weight (CG). Sweating was induced by 1) pilocarpine 1% iontophoresis (PILO); and 2) by passive heating (HEAT) via the lower third of the legs being immersed in 42°C water for one hour. Previously established eccrine sweat function and VTR protocols were used. Results The NF1 group showed: a) lower sweat rate than the CG group during PILO; b) a smaller diastolic pressure decrease; and c) higher tympanic temperatures than controls during HEAT (p < 0.05). Conclusion Reduced sweating and vascular thermoregulatory responses suggest autonomic dysfunction in NF1 individuals.